Once upon a time in the west [videorecording (DVD)] - Leone, Sergio, 1929-1989; Cardinale, Claudia, 1939-; Bronson, Charles, 1921-2003; Fonda, Henry, 1905-1982; Robards, Jason (Paramount, 2003)
A man preparing to welcome his new wife to his home is killed, along with his entire family.